The interplay between consumer protection and competition law in India. (5th June 2017) - Nathani, Suhail; Akman, Pınar
ABSTRACT: The protection of the interests of consumers is a central aspect of all modern competition laws as well as a direct aim of consumer protection laws. However, despite being complementary in many ways, competition and consumer protection laws cover different issues and employ different methods to achieve their goals. While consumer protection rules are built upon the premise that consumers are the weaker party to transactions and should be directly protected for this reason in their dealings with traders through certain consumer rights, competition law only indirectly protects the consumers' economic well-being by ensuring that the markets are subject to effective competition. This article explores the interplay between consumer protection and competition law in the Indian context with some comparison with the EU position, where relevant. After an examination of the relevant legislation and case law, the article finds that given that the mandate of the Competition Commission of India is to prevent practices having an adverse effect on competition, in cases of overlap between consumer protection and competition laws, the Authority should act only on the basis of adverse effects on competition . The treatment of 'unfair trade practices' is used to demonstrate the appropriateness of this approach.